Aerosol-jet printing facilitates the rapid prototyping of microfluidic devices with versatile geometries and precise channel functionalization. (June 2020) - Ćatić, Nordin; Wells, Laura; Al Nahas, Kareem; Smith, Michael; Jing, Qingshen; Keyser, Ulrich F.; Cama, Jehangir; Kar-Narayan, Sohini
Highlights: Aerosol-jet printing is used to fabricate microfluidic devices with customised geometries, including steps and slopes. A rapid prototyping method for producing bespoke molds for microfluidic devices with precise channel functionalization. The functionalization capability is demonstrated by rendering a section of a microfluidic channel hydrophilic using PVA. Abstract: Microfluidics has emerged as a powerful analytical tool for biology and biomedical research, with uses ranging from single-cell phenotyping to drug discovery and medical diagnostics, and only small sample volumes required for testing. The ability to rapidly prototype new designs is hugely beneficial in a research environment, but the high cost, slow turnaround, and wasteful nature of commonly used fabrication techniques, particularly for complex multi-layer geometries, severely impede the development process. In addition, microfluidic channels in most devices currently play a passive role and are typically used to direct flows. The ability to "functionalize" the channels with different materials in precise spatial locations would be a major advantage for a range of applications. This would involve incorporating functional materials directly within the channels that can partake in, guide or facilitate reactions in precisely controlled microenvironments. Here we demonstrate the use of Aerosol Jet Printing (AJP) to rapidly produce bespoke molds for microfluidic devices with a range of different geometries and precise "in-channel" functionalization. We show that such an advanced microscale additive manufacturing method can be used to rapidly design cost-efficient and customized microfluidic devices, with the ability to add functional coatings at specific locations within the microfluidic channels. We demonstrate the functionalization capabilities of our technique by specifically coating a section of a microfluidic channel with polyvinyl alcohol to render it hydrophilic. This versatile microfluidic device prototyping technique will be a powerful aid for biological and bio-medical research in both academic and industrial contexts.